Using cloud computing for stem education in general school - Soroko, Nataliia Volodymyrivna (Studies in Comparative Education, 2018)
The article is devoted to the problems of using cloud services for the STEM-education support in a general school. There is considered the foreign experience of solving the main issues on the implementation of STEM-oriented approach at all educational levels with the help of information and communication technologies. The purpose of the article is to analyze the foreign experience of using cloud computing services for the STEM-education support of a general school and highlight the main problems in this process. It is concluded that STEM-education is one of the most important areas of development education system and education reform, which is explained by the significant demand of the world labor market for specialists in the STEM industries. To ensure effective implementation of the STEM-oriented approach in the study of the general educational institution at all education levels is the use of information and communication technologies, in particular cloud services.